The Impact of International Financial Reporting Standards on Global Accounting Practices - Lawalata, Josina; Salle, Ilham Z; Yuliana, Leny (Advances in Applied Accounting Research, 2024)
Purpose: This study examines the impact of International Financial Reporting Standards (IFRS) on global accounting practices, with a focus on financial reporting quality, economic outcomes, and the influence of regulatory and cultural contexts. Research Design and Methodology: A mixed-methods approach was employed, combining qualitative interviews with accounting professionals and quantitative analysis of financial statements from various countries. The study examines the benefits and challenges of IFRS adoption, taking into account factors such as regulatory environments, cultural differences, and varying levels of economic development. Findings and Discussion: The findings reveal that IFRS adoption enhances financial reporting quality by increasing transparency, reducing earnings management, and improving the comparability of financial statements. These benefits are most pronounced in countries with strong regulatory frameworks. However, challenges include high costs and complexities of the transition process, especially for smaller firms and developing countries. Cultural and institutional factors significantly influence the effectiveness of IFRS adoption, with varying impacts across different economic contexts. Implications: The study's results underscore the importance of supportive regulatory environments and comprehensive training for accounting professionals in facilitating the effective adoption of IFRS. Policymakers and regulators should consider tailored approaches to address specific challenges faced by different countries. Companies, particularly in developing regions, must plan and allocate resources carefully to manage the transition to IFRS. These insights offer practical guidance for enhancing the effectiveness of IFRS implementation worldwide.